1989
DOI: 10.1073/pnas.86.19.7366
|View full text |Cite
|
Sign up to set email alerts
|

A 13-amino acid peptide in three yeast glycosyltransferases may be involved in dolichol recognition.

Abstract: Contributed by Phillips W. Robbins, June 30, 1989 ABSTRACT A 13-amino acid peptide was identified in three glycosyltransferases of the yeast endoplasmic reticulum. These enzymes, the products of the ALGi, ALG7, and DPMI genes, catalyze the transfer of sugars from nucleotide sugars to dolichol phosphate derivatives. The consensus sequence for the conserved peptide was Leu-Phe-Val-Xaa-Phe-Xaa-XaaIle-Pro-Phe-Xaa-Phe-Tyr. A sequence resembling the conserved peptide was also found in the predicted SEC59 protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…Beyond catalysis, it is likely that this protein contains some specificity for the lipid portion of its substrate. Previous studies have identified a potential isoprenol recognition sequence for dolichol (FI/VxF/YxxIPFxF/Y) which we were unable to identify in BacA/UppP (Albright et al, 1989;Datta & Lehrman, 1993). We therefore hypothesize that the residues exhibiting identity in the first transmembrane domain constitute an undecaprenol recognition motif.…”
Section: Baca/uppp: the Principal Undecaprenyl Pyrophosphate Phosphatmentioning
confidence: 48%
“…Beyond catalysis, it is likely that this protein contains some specificity for the lipid portion of its substrate. Previous studies have identified a potential isoprenol recognition sequence for dolichol (FI/VxF/YxxIPFxF/Y) which we were unable to identify in BacA/UppP (Albright et al, 1989;Datta & Lehrman, 1993). We therefore hypothesize that the residues exhibiting identity in the first transmembrane domain constitute an undecaprenol recognition motif.…”
Section: Baca/uppp: the Principal Undecaprenyl Pyrophosphate Phosphatmentioning
confidence: 48%
“…Thus, it is highly possible that those lysine residues that are proximal or within the transmembrane domains of OT subunits are involved in cross-linking among them. Indeed, this idea was further supported by the cross-linking of OT subunit Ost1p Ost1p with another ER membrane protein, Alg1p, with regard to their relationship as follows: several OT subunits (Ost1p, Wbp1p, Swp1p) were found containing the consensus sequence, which is distinctive among dolichol binding enzymes in their membrane-spanning domains and has been proposed to bind to the assembled lipid-linked oligosaccharides (25,26), and Alg1p was recently found to exist as a homo-oligomer and perform dual functions in sugar transfer and in the recognition of dolichol phosphate-derived substrates. 2 Therefore, Alg1p could serve as a good model to investigate our hypothesis if it ideally interacts with one or more OT subunits that are involved in recognition and the binding of lipid-linked oligosaccharide donors.…”
Section: Selectivity Of the Cross-linker-as Demonstrated Inmentioning
confidence: 86%
“…3c). A potential dolichol recognition sequence located in transmembrane domains of several dolichol-utilizing enzymes has been proposed (30). However, in the ALG8 glucosyltransferase sequence no region with a high homology to the potential dolichol recognition sequence F (I/V)X(F/Y)XXIPFX(F/Y) (30,31) was detected.…”
Section: Discussionmentioning
confidence: 99%
“…A potential dolichol recognition sequence located in transmembrane domains of several dolichol-utilizing enzymes has been proposed (30). However, in the ALG8 glucosyltransferase sequence no region with a high homology to the potential dolichol recognition sequence F (I/V)X(F/Y)XXIPFX(F/Y) (30,31) was detected. Direct evidence for the involvement of this sequence in the recognition or binding of dolichol is not available, but mutational analysis of this potential dolichol recognition sequence in hamster GlcNAc-1-phosphate transferase revealed that this sequence is essential for enzymatic activity (32).…”
Section: Discussionmentioning
confidence: 99%